Dynamics of Religious Conflict and Social Movements in Society - Martunis Martunis; Zulfikar Zulfikar; Marwan Marwan; Mukhlis Mukhlis; Darmadi Darmadi (Sean Institute, 2026)
Religion is a social institution that plays a crucial role in shaping societal values, identity, and solidarity. However, in practice, religion also has an ambivalent character, serving as both a source of social integration and a trigger for conflict. On the other hand, social and political conflict often fosters the emergence of religion-based social movements that utilize religious values ​​as a moral foundation in their struggle for justice and social change. This article aims to analyze the dynamics of the relationship between religion, conflict, and social movements in society through a sociological perspective. The study employed a literature review method with a descriptive qualitative approach, analyzing various sociological theories of religion, conflict theory, social movement theory, and relevant previous research findings. The discussion demonstrates that religion has a dual capacity as a source of social cohesion and conflict, depending on the social, political, and economic context, as well as the interpretation of religious teachings. Conflict can strengthen religious identity and trigger the birth of religion-based social movements that derive moral legitimacy, organizational structure, and collective motivation from religious values. The case study of the communal conflict in Poso demonstrates that religion-based conflict does not exist in isolation but is influenced by the interaction of social, economic, political, and identity factors. Therefore, understanding the relationship between religion, conflict, and social movements requires a multidimensional approach to be able to explain the role of religion more comprehensively as a factor that can drive conflict or become a force for social transformation towards peace and justice.